Catalytic asymmetric alkylation reactions for the construction of protected ethylene-amino and propylene-amino motifs attached to quaternary stereocentres. - Moss, T; Barber, D; Kyle, A; Dixon, D (2013)
An efficient catalytic and stereoselective method for the direct construction of protected ethylene-amino and propylene-amino scaffolds attached to quaternary stereocentres is reported. Preliminary investigations revealed a mild base catalysed nucleophilic ring opening of N-sulfonyl aziridines using the commercially available phosphazene base 2-tert-butylimino-2-diethylamino-1,3-dimethyl-perhydro-1,3,2-diazaphosphorine (BEMP) was possible and resulted in highly efficient alkylation reactions with a range of methine carbon acids. This reaction could be rendered highly asymmetric (up to 97% ee) by employing phase-transfer catalysis to control stereoinduction. Incorporation of alkyl substituents onto the aziridine electrophile, resulted in a highly diastereoselective (up to 30:1 d.r.) variant of this methodology. A further extension using N-protected cyclic sulfamidates as the electrophilic component was successful with a range of pro-nucleophiles (up to 96% ee and 45:1 d.r.) and allowed a range of nitrogen protecting groups (carbamate, sulfonyl, phosphonyl, benzyl) to be incorporated into the alkylation adducts. Finally, the utility of the products have been demonstrated in the synthesis of useful heterocycles and compounds bearing structural components of natural products.